THE EFFECTIVENESS OF 'LUDO GENTING' GAME ON ADOLESCENT HEALTH KNOWLEDGE - Octovia Manalu, Lisbet; Dinta (STIKes Budi Luhur Cimahi, 2025)
Anemia and stunting remain critical public health issues in Indonesia. As of 2023, 32% of adolescent girls were affected by anemia, while stunting impacted 21.6% of children. These conditions are largely driven by poor nutrition and limited health education. Educational games have been shown to be more effective in enhancing knowledge and promoting healthy behaviors compared to traditional lecture-based methods. Game-based learning is increasingly recognized as an innovative and engaging approach to health education, especially among adolescents. This study aimed to assess the effectiveness of the educational game “Ludo Genting” in improving adolescents’ knowledge about anemia, nutrition, and stunting in Bandung. A quantitative pre-experimental study was conducted using a one-group pre-test and post-test design. The study involved 48 adolescents selected through quota sampling. Data were collected using structured questionnaires administered before and after the intervention. The findings revealed a notable increase in adolescents' knowledge following the intervention. In the 10–14 age group, 12 out of 16 participants (75%) demonstrated good knowledge levels. The same percentage (75%) was observed in the 15–19 age group. In the 20–24 age group, 13 out of 16 participants (81.25%) achieved a good knowledge category, indicating a positive impact of the game across all age segments. “Ludo Genting” proved to be an effective educational tool for enhancing adolescent knowledge on anemia, nutrition, and stunting. The results showed a statistically significant improvement with a p-value of <0.001.Keywords: Adolescent, Anemia, Nutrition, Stunting, Game education